Analisis pengaruh jumlah tenaga kerja, tingkat pendidikan dan investasi terhadap pertumbuhan ekonomi melalui kesempatan kerja di Provinsi Jambi - Fahrizal, Fahrizal; Zamzami, Zamzami; Safri, Muhammad (Jurnal Paradigma Ekonomika, 2021)
This study aims to: 1) To analyze the effect of the number of workers, the level of education and investment on economic growth in Jambi Province 2000-2018. 2) To analyze the effect of the amount of workforce, level of education, and investment on economic growth through employment opportunities in Jambi Province 2000-2018. The effect of labor, education, and investment on economic growth in Jambi Province during the period 2000 to 2018. Labor, education, and investment simultaneously affect economic growth in Jambi Province with R2 of 98.4 percent. Meanwhile, if seen partially, the three independent variables, namely labor, education, and investment have a significant effect on economic growth in Jambi Province, the influence of labor, education, investment, and economic growth on employment opportunities as an intervening variable in Jambi Province during the period 2000 to 2018. It can be concluded that labor, education, investment, and economic growth simultaneously have a significant effect on job opportunities, while partially labor and education have a significant effect on job opportunities in Jambi Province, while investment and economic growth have no significant effect on employment opportunities with R2 of 98,6 percent Â